ANALISIS ORGANOLEPTIK DODOL PISANG RAJA (Musa paradisiaca L.) DENGAN SUBSTITUSI TEPUNG Wikau maombo - Supiani, Supiani (Jurnal Sains dan Teknologi Pangan, 2016)
Dodol is a semi wet food because it has 20% of  moisture content. This research aimed to determine the organoleptic banana’s dodol selected. The first factor is the type of flour (W) consisting of two levels ie wikau maombo flour sweet (W1) and bitter (W2) varieties. The second factor is the concentration of the addition of glutinous rice flour (T) consisting of five levels ie addition of glutinous rice flour 0% (T0), the addition of glutinous rice flour 10% (T1), the addition of glutinous rice flour 15% (T2), the addition of rice flour glutinous 25% (T3), the addition of glutinous rice flour 100% (T4). Organoleptic test method used is by using a hedonic scale. The results showed that the wikau maombo flour substituted with glutinous rice in products banana’s dodol good effect on the assessment of organoleptic panelist, banana’s dodol from the substitutions chosen are treatments W2T3 (flour wikau maombo varieties of bitter 75% and the addition of glutinous rice flour 25%). The type of cassava against banana’s dodol products preferred panelist is wikau maombo flour bitter varieties. Wikau maombo flour formulations, banana’s dodol products preferred panelists, namely composition of wikau maombo flour bitter varieties of 75% and the addition of glutinous rice flour 25%. The results of organoleptic with  color parameter on the selected treatment is 3.83 (like), aroma 3.82 (like), the texture of 3.84 (like) and a sense of 3.80 (like). Key word : Banana’s (Musa aradisiaca L.) dodol , Organoleptic, glutinous rice flour, wikau maombo flour.